Correlation of tear cortisol levels with morphological and biomechanical parameters of keratoconus - Zhao, Xiaorui; Sun, Tong; Yuan, Yifei; Zhang, Yu; Chen, Yueguo; Hong, Jing (Frontiers in Medicine, 2025)
IntroductionKeratoconus (KC) is a vision-threatening corneal disorder predominantly affecting young males, significantly impairing their quality of life. We aim to evaluate tear cortisol levels in KC and compare with controls, and to determine the correlation of tear cortisol levels with morphological and biomechanical parameters of KC.MethodsAge- and sex-matched 42 eyes of 42 patients were enrolled. The levels of tear cortisol were obtained by liquid chromatography–tandem mass spectrometry. Pentacam HR and Corvis ST II were used to detect the corneal morphological and biomechanical parameters. Spearman correlations between tear cortisol levels and corneal parameters were calculated for all patients.ResultsComparing with the control group, the level of tear cortisol significantly increased in the KC group (1660.95 [1175.01–2408.81] vs. 945.60 [550.36–1699.32], p = 0.023). It was positively correlated with Belin-Ambrosio Display D value (BAD-D), inferior–superior value (IS-value), keratoconus index (KI), Pentacam random forest index (PRFI), Corvis biomechanical index (CBI), and negatively correlated with central corneal thickness (CCT) and thinnest corneal thickness (TCT). No significant association was found between tear cortisol levels and maximum K value (Kmax), tomographic and biomechanical index (TBI), and stress–strain index (SSI).ConclusionOur findings demonstrate that tear cortisol levels are significantly associated with some corneal morphological and biomechanical parameters in KC, suggesting its potential role as a pathogenic factor, thereby providing new insights into the exploration of disease pathogenesis.